أثر تطبيق متطلبات نظام الرقابة الداخلية على الأداء المالي في المؤسسات الإقتصادية الجزائرية - keblouni, hamza; saidani, mouhamed said (Finance and Business Economies Review, 2018)
The main objective of this study is focused on the ability to implement the internal control requirements in the Algerian economic enterprise, as well as their impact on the financial performance. To do a study tool (the questionnaire) was performed which consists of 25 paragraphs. The representative sample of the population studied are the internal auditor’s economic companies selected, our case does not affect the financial performance of the size compared to return on assets, the rate of return sales and the rate of return on the equity ratio.